Primary chaetotaxy and morphometry of the head capsule and head appendages of first instar larvae of Chaetarthria bruchi (Coleoptera: Hydrophilidae: Chaetarthriinae: Chaetarthriini) - Archangelsky, Miguel (2021)
The primary chaetotaxy of the head capsule and head appendages of the larvaof Chaetarthria bruchi Balfour-Browne is described for the first time. Morphometric charactersderived from the head capsule and mouthparts are included, together with detailedillustrations of all characters. Chaetotaxy of C. bruchi is compared with that of C. seminulum(Herbst), the only other Chaetarthriini species for which the chaetotaxy has been described.RESUMEN. La quetotaxia primaria de la cápsula cefálica y de los apéndices cefálicos dela larva de Chaetarthria bruchi Balfour-Browne se describen por primera vez. Caracteresmorfométricos derivados de la cabeza y sus apéndices son incluidos junto con ilustracionesdetalladas de todos los caracteres. La quetotaxia de C. bruchi se compara con la de C.seminulum (Herbst), la única otra especie de Chaetarthriini para la cual se ha descripto laquetotaxia.